2018
DOI: 10.1371/journal.pone.0196656
|View full text |Cite
|
Sign up to set email alerts
|

Sensing CA 15-3 in point-of-care by electropolymerizing O-phenylenediamine (oPDA) on Au-screen printed electrodes

Abstract: This work presents an alternative device for cancer screening in liquid biopsies. It combines a biomimetic film (i) with electrochemical detection (ii). The biomimetic film (i) was obtained by electro-polymerizing amine-substituted benzene rings around a CA 15–3 target. This protein target was previously adsorbed on a gold (Au) support and incubated in charged monomers (4-Styrenesulfonate sodium and 3-Hydroxytyraminium chloride). The protein was further eliminated by enzymatic activity, leaving behind vacant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The time given for incubation was typically set from 15 to 30 min. In general, longer times may improve sensitivity as there is more time to allow Cys-C adsorption, while shorter times may improve selectivity as there is little time for non-specific adsorption [33,34]. Therefore, as a compromise, without further experiments for this selection, the incubation time was set to an intermediate value of 20 min.…”
Section: Analytical Performance Of the Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The time given for incubation was typically set from 15 to 30 min. In general, longer times may improve sensitivity as there is more time to allow Cys-C adsorption, while shorter times may improve selectivity as there is little time for non-specific adsorption [33,34]. Therefore, as a compromise, without further experiments for this selection, the incubation time was set to an intermediate value of 20 min.…”
Section: Analytical Performance Of the Sensormentioning
confidence: 99%
“…tion [33,34]. Therefore, as a compromise, without further experiments for this selection, the incubation time was set to an intermediate value of 20 min.…”
Section: Analytical Performance Of the Sensormentioning
confidence: 99%
“…They used label-free impedance to detect VEGF with a dynamic range from 20 to 200 pg mL −1 and a limit of detection of 0.08 pg mL −1 [ 146 ] ( Figure 11 ). Gomes et al developed an electropolymerized SPE with amine-substituted benzene rings as monomers and specifically charged monomers for creating protein imprinting materials for breast cancer biomarker CA 15-3 [ 147 ]. The commercial Au SPE from DropSens consists of gold working and auxiliary electrodes, and reference and electrical contacts made of silver.…”
Section: Screen Printingmentioning
confidence: 99%
“…The commercial Au SPE from DropSens consists of gold working and auxiliary electrodes, and reference and electrical contacts made of silver. Using this sensor, Gomes et al demonstrated a linear dynamic range of 0.25 to 20.00 U mL −1 , with detection limit of 0.05 U mL −1 , for CA 15-3, from square wave voltammograms in diluted serum, with only 15 min incubation between sensor and solution of CA-15-3 [ 147 ].…”
Section: Screen Printingmentioning
confidence: 99%
“…The electrically conductive nature of noble metal nanoparticles offers the possibility of combining electrochemical and optical sensing capabilities on a single substrate, and in combination with transparent conducting oxides (TCOs) allow for convenient optical studies of electrochemically induced perturbations in resonance conditions [9,10]. Electrochemical processes at metallic surfaces, including micro and nanostructures, are advantageous in the preparation of sensing devices with polymeric ligands (e.g., molecular imprint polymers-MIP) [11,12]. MIP layers can be prepared at plasmonic surfaces by bulk polymer synthesis [13] but control of film growth is difficult.…”
Section: Introductionmentioning
confidence: 99%